The Role of Product Innovation to Support Brand Image and Word of Mouth Communication in Improving Customer Satisfaction - Nurjanah; Thamrin Abdullah; Jubery Marwan (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
This study's objective is to investigate and assess the role that product innovation plays in contributing to the enhancement of brand image and word-of-mouth communication in order to improve consumer satisfaction. In Jakarta, automobile showrooms served as the locations for the research that was carried out using an explanatory design and a quantitative methodology. Path analysis was used as the analytical tool, and a saturation sampling technique was used to acquire the primary data. These data were then verified for validity, reliability, and homogeneity after they were obtained. According to the findings, factors such as brand image and word-of-mouth communication have a considerable impact on product innovation and customer satisfaction. Furthermore, the findings indicate that product innovation itself has a powerful and decisive influence on consumer satisfaction. In addition, the innovations that are made to products have an indirect impact on the level of happiness that customers have with the brand. The research also highlights the fact that consumers' actual experiences with a product shape their references and recommendations to others. Furthermore, the study highlights that when word-of-mouth communication is reinforced by product innovations that emphasize quality, durability, uniqueness, technological transformation, diverse variants, and stylish design, the combined effect significantly enhances customer satisfaction.